2017
DOI: 10.1007/s00270-017-1713-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic and Clinical Outcomes After Treatment of Femoro-Popliteal Lesions with a Novel Paclitaxel-Matrix-Coated Balloon Catheter

Abstract: The use of paclitaxel-resveratrol-matrix-coated peripheral balloon angioplasty as compared to POBA was associated with significantly reduced in-lesion LLL and reduced TLR rates. ClinicalTrials.gov identifier NCT01970579.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…We included a total of 22 RCTs. Seventeen trials compared DCB to POBA in FPD 4,5,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] and five RCTs compared DCB to POBA in patients with ISR with a previous stent to FPD. [27][28][29][30][31]…”
Section: Data Extractionmentioning
confidence: 99%
“…We included a total of 22 RCTs. Seventeen trials compared DCB to POBA in FPD 4,5,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] and five RCTs compared DCB to POBA in patients with ISR with a previous stent to FPD. [27][28][29][30][31]…”
Section: Data Extractionmentioning
confidence: 99%
“…The primary end point of in‐lesion late lumen loss (LLL) at 6 months and target lesion revascularization (TLR) at 12 months were superior in the DCB group: (LLL 0.35 mm vs 0.72 mm, P = 0.006), and (TLR 17.8 vs 37.7%, P = 0.008). There was also improved censored walking distance in DCB group in comparison to balloon angioplasty group …”
Section: Interventional Trials In Lower Extremity Padmentioning
confidence: 99%
“…There was also improved censored walking distance in DCB group in comparison to balloon angioplasty group. 7…”
mentioning
confidence: 99%
“…Numerous randomized trials on femoropopliteal artery disease demonstrated that drug-coated balloon (DCB) angioplasty effectively decreased late lumen loss (LLL) [1][2][3][4][5][6][7][8][9] and increased primary patency [10][11][12][13][14]. However, heterogeneity among studies is substantial: The mean number of patients needed to treat within 1 year to prevent a single target lesion revascularization (TLR) ranges between 4 and 33 [15].…”
Section: Introductionmentioning
confidence: 99%